TRANSMITTING ISLAM THROUGH STORIES: The Sociology of Production and Consumption of Islam in Novel Literature (State Islamic University (UIN) of Sunan Ampel Surabaya, 2017)
Islamic novel literature has become a new commodity in Indonesia. This paper examines the Islamic creative and cultural industry in recent development in Indonesia, exploring the Islamic publication through its exploitation of storytelling method as a means of production and consumption of Islamic commodities. As an object of analysis, it focuses on Islamic novel Ayat-Ayat Cinta. It particularly argues that Islamic publication has extended its capacity as a medium for transmitting religious ideas to producing and consuming economic commodities. It further argues that storytelling appears to be an effective method for both the transmission of Islamic teaching and the production and consumption of Islamic commodities. It maintains that positive responses from the market are not only in the form of purchasing the product of Islamic novel literature, but also in the form of following up the essence of cases in life exploited in stories developed in such an Islamic novel literature.